THE EFFECT OF LIQUIDITY, SOLVABILITY, PROFITABILITY AND SIZE RATIO ON STOCK PRICE (Case study on Coal Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) - Chieka Putri Anjani; Nurni Arrina Lestari; Antony (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to determine the effect of Current Ratio, Debt to Equity Ratio, Return on Equity Ratio, Net Profit Margin and Firm Size on Stock Prices. The sample in this study is the Coal Mining Sub-Sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling technique in this study uses purposive sampling, where there are 12 Coal Mining Sub-Sector companies that meet the criteria. The analytical methods used in this study are the classic assumption test, correlation coefficient test, determination coefficient test, multiple linear regression test and hypothesis test consisting of t-test and f-test using the Statistical Package for the Social Science (SPSS) version 26 program with the Entel method and Microsoft Excel for Windows 2010. The results of the study indicate that partially CR, NPM, Firm Size do not have a significant effect on Stock Prices. Debt to Equity and Return on Equity have a significant effect on Stock Prices. Simultaneously CR, DER, ROE, NPM, Size have an effect on Stock Price.